#Budolfinds: The Role of TikTok’s Shopee Finds’ Videos in the Impulsive Buying Behavior of Generation Z Consumers - Barcelona, Alvin B.; Angeles, Rhea Jane G.; Clemente, Carmhiella A.; Dela Cruz, Sam Rhoy B.; Malimban, Renoa Lorraine O.; Santos, Jean Erika G.; Tan, Jian Carlo D. (Future Science / FSH-PH Publications, 2022)
The continuous growth of social media platforms in the market has influenced the consumption of different products and services. The proliferation of short user-generated videos, such as TikTok’s Shopee Finds was hypothesized to influence impulsivity among young consumers. This study employed a descriptive survey administered online to 200 Generation Z respondents. Descriptive and inferential statistics were used to analyze the data. The findings revealed that TikTok’s Shopee Finds moderately influenced the Pure Impulse and Suggested Impulse Buying behaviors of the respondents. Moreover, it highly influenced the Reminder Impulse and Planned Impulse Buying behaviors of the respondents. There is no sex difference in the impact of the marketing videos on the impulsive behavior of the respondents. The preliminary findings entail further opportunities for businesses and enterprises to optimize their marketing efforts using social media platforms and increase the awareness of Generation Z consumers about their impulsive buying tendencies.